Protection System for Electrical Loads of Administration Building in Controlling Voltage Variations Due to Over-Voltage and Under-Voltage - Camacho, John Bryan S.; Cinense, Erlan L.; Guzman, Christian Philip P. De; Garcia, Gian Irby L.; Pampo, Freneil R.; Canlas, Errol M. (Universitas Pendidikan Indonesia (UPI), 2023)
The purpose of this study is to focus on producing a protection system design for the electrical loads of administration buildings from over and under voltage. An on-site voltage reading has been initiated and continued for several days to determine whether voltage variation is occurring in the location. The building’s load schedule has served as a point of reference in calculating the appropriate size of wire and Molded Case Circuit Breaker ampere rating. For the proponents to understand the design standards, the Philippine Electrical Code is used as a reference. Consequently. The design that has been made and proposed is for controlling over and under voltages. The power supply at the Administration building can be transferred over to the other power supply coming from a generator set. The voltage readings in the Admin Office MDP range from 218.55 to 231.03 V. The other one on the General Office MDP is from 219 to 230.48 V, showing that no over-voltage and under-voltage is happening in the building and normal working voltages are delivered on the electrical loads. Thus, the electrical loads in the building are safe from voltage variations.